2022
DOI: 10.3390/jcm11237146
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Response to Affective Touch in Children with Autism: Multi-Parametric Exploration of the Autonomic System

Abstract: This study aimed at evaluating the autonomic response to pleasant affective touch in children with Autism Spectrum Disorders (ASD) and age-matched typically developing (TD) peers, thanks to multiple autonomic nervous system (ANS) parameters and by contrasting CT (C-tactile fibers) high- vs. low-density territory stimulations. We measured pupil diameter, skin conductance, and heart rate during gentle stroking of two skin territories (CT high- and low-density, respectively, forearm and palm of the hand) in thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 142 publications
0
5
0
Order By: Relevance
“…While recent studies have delved into understanding the physiological responses associated with affective touch in neurotypical individuals (Chatel-Goldman et al, 2014;Mazza et al, 2023;Triscoli et al, 2017), the only study that has focused on autonomic responses to affective touch in children with ASD has reported an overall hypoactivation in ASD children compared to TD peers (Bufo et al, 2022). Bufo et al (2022) have proposed that the diminished autonomic activation observed in ASD children when receiving affective touch could be attributed to a reduced engagement reaction commonly found in the ASD population. This reaction is likely influenced by both a lack of social motivation (Chevallier et al, 2012), and a deficiency in rewarding experiences associated with touch in general (Gordon et al, 2016) typical of the ASD subjects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While recent studies have delved into understanding the physiological responses associated with affective touch in neurotypical individuals (Chatel-Goldman et al, 2014;Mazza et al, 2023;Triscoli et al, 2017), the only study that has focused on autonomic responses to affective touch in children with ASD has reported an overall hypoactivation in ASD children compared to TD peers (Bufo et al, 2022). Bufo et al (2022) have proposed that the diminished autonomic activation observed in ASD children when receiving affective touch could be attributed to a reduced engagement reaction commonly found in the ASD population. This reaction is likely influenced by both a lack of social motivation (Chevallier et al, 2012), and a deficiency in rewarding experiences associated with touch in general (Gordon et al, 2016) typical of the ASD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…This reaction is likely influenced by both a lack of social motivation (Chevallier et al, 2012), and a deficiency in rewarding experiences associated with touch in general (Gordon et al, 2016) typical of the ASD subjects. However, in their pioneering work Bufo et al (2022) did not contrast the physiological response to affective touch with any other type of control touch. In contrast, our experiment uncovered this critical point by showing that while autonomic responses to affective touch were greater than those to control touch in TD individuals, participants with ASD exhibited comparable levels of activation between the two types of touch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 83 Future research on interoception at early processing levels, such as the function of peripheral small fibers and the relation to the autonomic regulation, could also contribute to the understanding of some behavioral and social symptomatology experienced by autistic individuals. 107 , 140 …”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that in autism, there may be differences in inhibitory mechanisms needed to reallocate physiological resources in response to external factors. 106 Along this line, in both autistic and non-autistic children, Bufo et al 107 collected autonomic parameters during gentle tactile stimulation in two skin regions, one corresponding to high-intensity C fibers (forearm), and the other to low-intensity C fibers l (palm of the hand). In response to tactile stimuli on both skin regions, non-autistic children had an increase in pupil diameter and skin conductance, along with a decrease in heart rate.…”
Section: Neural Characteristic Of Autism: Implications On Interoceptionmentioning
confidence: 99%